Experimental study of flow and heat transfer in rectangular ducts with ribbed surfaces (2022)
The Pivotal focus on fluid and thermal equipment performance have remained to directly lower energy cost by utilizing varieties of surface structures including extended surfaces, treated surfaces, and rough surfaces. This has necessitated the resurgence of surfaces with dimples and protrusions for an enhanced system efficiency in electronic components, gas turbine blade cooling, vortex creation on air foil structures, combustion chambers, printed circuit boards, microfluidic passageways, and heat exchangers features. In this study, the performance characteristics, heat transfer enhancement (Nu/Nuo), friction factor ratio (f/fo), and overall thermal performance (OTP) of two test channels with distinct surface structures. The performance parameters were evaluated using experimental rigs, one with continuous spiral rib channel and the other one with discontinuous spiral rib channel. Thereafter, the results from both test channels were compared to a smooth surface channel. Comparing the performance characteristics, Nu/Nuo, f/fo, and OTP of the discontinuous spiral rib and continuous spiral rib were 31.5%, 91.3%, 4.4% and 81.9%, 113.6%, 38.4% higher than the smooth surface spiral rib channel. Finally, the study shows that the continuous spiral rib channel gave a lower pressure loss, and was established to possess higher heat transfer coefficient and overall thermal performance than the discontinuous spiral rib channel.